Renegotiation of identity in young adults with cancer: A longitudinal narrative study. (February 2020) - Pearce, S.; Whelan, J.; Kelly, D.; Gibson, F.
Abstract: Background: Despite increasing international awareness of the impact of cancer on young adults, to date there has been limited in-depth research to understand their experiences following a diagnosis using a qualitative and longitudinal perspective. Objectives: To explore the impact of cancer on young adults' evolving sense of self and identity over one year from the time of diagnosis. In addition, to contribute further to an understanding of innovative research methods used to examine this experience. Design: This was a longitudinal narrative study using visual methods and a psychosocial lens. Narrative was used to re-present experiences over time. Setting and Sample: Recruitment was from a Principal Treatment Centre for Teenagers and Young Adults with Cancer and a Cancer Centre for Adults in the United Kingdom. Total population sampling was used over a six-month period, recruiting 18 young adults aged between 16 and 30, one to three months from a diagnosis of bone cancer, lymphoma or leukaemia. Methods: In depth, free association narrative interviews at three-time points over a year were undertaken. Photographs were used to help with story-telling. Extensive reflexive field notes, debriefing and the use of a psychosocial research group, also formed data sources. Forty interviews were conducted with 18 participants: eight took part in three interviews, six in two interviews and four in one interview. Analysis focused on the holistic 'case' of the individual temporally. In-depth, visual images were analysed from discussion in the narrative text. Through memoing, coding and comparison, themes were developed across all cases and a conceptual framework developed. Results: The conceptual framework illustrates the renegotiation of self over time through narrative. This was 'biographically' during young adult development and across 'cancer time'; through the core components of: the inner world, (psyche, emotion and coping); self as embodied; self as relating to others, and self as relating to place. Stories indicated that there was a constant inter- relationship over time between the renegotiation of identity and adaption of biography. Conclusions: The focus in this paper is on 'the temporality of cancer' through the first year from diagnosis, and the juxtaposed process of managing biographical and developmental milestones. The importance of developing health care and research which enables narrative and the patient's voice has been highlighted. It emphasises the need for professionals to 'be with' and 'walk alongside' through the intensity of a biographically and identity changing illness. Using longitudinal narrative, visual & psychosocial methods to describe the impact of a diagnosis of cancer on young adults' sense of biography and identity.